2009
DOI: 10.1158/1078-0432.ccr-09-0522
|View full text |Cite
|
Sign up to set email alerts
|

A Phase I Study of a 2-Day Lapatinib Chemosensitization Pulse Preceding Nanoparticle Albumin-Bound Paclitaxel for Advanced Solid Malignancies

Abstract: Purpose: Systemic chemotherapy fails to access much of the tumor burden in patients with advanced cancer, significantly limiting its efficacy. In preclinical studies, brief high doses of tyrosine kinase inhibitors (TKI) targeting the human epidermal growth factor receptor (HER) family can prime tumor vasculature for optimal chemotherapeutic delivery and efficacy. This study investigates the clinical relevance of this approach. Experimental Design: A phase I clinical study of escalating doses of the HER TKI lap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 34 publications
2
23
0
1
Order By: Relevance
“…animals survived treatment, and hus, two consecutive daily treatments with high dose lapatinib was a tolerable regimen in our preclinical model. A recent phase clinical trial (25) demonstrated the safety of 2 pulse of dose lapatinib prior to administration of albumin-bound paclitaxel in solid malignancies, further supporting the clinical utility of the treatment paradigm we used in this study.…”
Section: Resultssupporting
confidence: 64%
“…animals survived treatment, and hus, two consecutive daily treatments with high dose lapatinib was a tolerable regimen in our preclinical model. A recent phase clinical trial (25) demonstrated the safety of 2 pulse of dose lapatinib prior to administration of albumin-bound paclitaxel in solid malignancies, further supporting the clinical utility of the treatment paradigm we used in this study.…”
Section: Resultssupporting
confidence: 64%
“…These nanoparticles are typically on the order of tens of nanometers to hundreds of micrometers in size (Ibrahim, Desai et al 2002; Wust, Gneveckow et al 2006; Curley, Cherukuri et al 2008; Chien, Illi et al 2009). Of the many forms of nanoparticles, some of the most clinically useful appear to be solid gold nanoparticles (AuNP) because of the presumed but yet unproven safety, the relatively simple and well described chemical reactions with gold, and relative ease of making defined sizes of these nanoparticles (Cherukuri, Glazer et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The concentrations required for those effects are well in the range of lapatinib concentrations determined in patients [61]. Thus, the observed effect of lapatinib on eryptosis may well contribute to or even account for its effect on anemia, a major side effect of the drug [9,11,25,26,61,62]. The sensitivity to lapatinib may be enhanced by clinical conditions known to enhance the susceptibility to triggers of eryptosis, such as dehydration [68], hyperphosphatemia [69], chronic kidney disease (CKD) [70][71][72][73], hemolytic-uremic syndrome [74], diabetes [75], hepatic failure [76], malignancy [63], sepsis [77], sickle-cell disease [63], beta-thalassemia [63], Hb-C and G6PD-deficiency [63], as well as Wilsons disease [78].…”
Section: Discussionmentioning
confidence: 86%
“…Lapatinib, an inhibitor of human epidermal growth factor receptor (HER) tyrosine kinases [1][2][3][4][5][6][7], is utilized in the treatment of malignancy [1,[8][9][10][11][12], such as breast cancer [2][3][4][5][6][7]. The drug is at least partially effective by triggering suicidal death or apoptosis of tumor cells [46][47][48][49][50][51][52][53][54][55][56][57].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation